Mainstreaming climate adaptation in spatial planning. The case of Baixa Pombalina in Lisbon - Ribeiro, Patrícia; Ferrão, João; Seixas, Júlia (Finisterra, 2018)
Baixa Pombalina is the historical downtown area of Lisbon city, close to the Tagus estuary, sheltering many economic activities with tourism at first. This paper assesses and maps the vulnerability of the area, at the neighbourhood scale, to floods episodes and sea level rise. The methodology outlines how the different components of vulnerability are tackled, while taking the importance of the local context to the definition of composite indexes. Twenty two vulnerability hotspots were found, for which six adaptation options are proposed to be embedded into Plano de Pormenor currently in place.